Creating More Livable Cities : The Case of the Rio de Janeiro Metropolitan Area - Palladini, Eric (World Bank, Washington, DC, 2012)
Despite Rio de Janeiro's privileged position as Brazil's historical capital (from the eighteenth century until 1960) and as a major center for tourism, culture, and education, the city and its region (collectively known as the metropolitan region of Rio de Janeiro) confronted significant challenges during the final decades of the twentieth century. Since the relocation of the national capital to Brasilia, ongoing industrial restructuring, and social inequality contributed to declines in the region's share of Brazil's population and gross domestic product (GDP). However, since 2001, the region has entered a new period of expansion, based on the surging petrochemical and metallurgical industries, and port and logistics services. Also promising for development over the coming years, the city will host the 2014 World cup final game and the 2016 summer Olympics. With this in mind, the World Bank, with a guarantee from Brazil's federal government, is funding the Rio de Janeiro metropolitan urban and housing Development Policy Loan (DPL).